Evaluación de niveles crecientes de energía en la suplementación de novillos de engorde en pastoreo - Ramírez-Barboza, José Ignacio (Instituto Tecnológico de Costa Rica, 2014)
The effect of racial component and energy supplementation steers grazing on production traits, carcass quality and cutting force was evaluated. The evaluation period was 144 days. The research was conducted in “La Vega” farm, this is located at San Carlos, Alajuela, Costa Rica. Used a total of 26 animals divided in three treatments, T0 (3,2 Mcal), T1 (3,4 Mcal) y T2 (3,67 Mcal). Productive characteristics were evaluated (daily gain (ADG) and final weight), characteristics in vivo carcass quality (marbling, muscle development and backfat), characteristics of carcass quality in slaughter (dressing percentage, backfat thickness (BFT), dental age, weight, perirenal fat and logissimus eye area (LEA)) and finally cutting force (CF) as a quality parameter of meat. No differences (p> 0.05) for production traits and carcass quality were found. An effect of racial component was found on meat quality (p <0.05), where European animals had smoothly meat in a maturation period of 14 days was found. It was also found that the inclusion of starchy raw materials in total ration performance enhancing meat quality.
Proyecto de graduación (Licenciatura en Ingeniería en Agronomía) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Agronomía, 2014
Keywords: Ganado de engorde; Pasturas; Calidad; Metabolismo